Impoliteness Strategies Used by Netizens in Benny Blanco’s Comment Section on Instagram - Sylvestrisa, Malva Prime Leveler; Suraiya, Lucy (Program Studi Sastra Inggris, 2025)
The purpose of this research is to analyze the types and functions of impoliteness strategies used by netizens in the comment section on Instagram of Benny Blanco, a celebrity who posted about his girlfriend, Selena Gomez. Fifty English comments in response to Benny Blanco’s Instagram post on July 22, 2024 were collected. Qualitative descriptive method and Culpeper’s impoliteness theory were used to analyze the data. The research results indicate that the bald on record is the dominant type of impoliteness that netizen used to respond Benny Blanco’s post with 24 data (48%). It is followed by positive impoliteness with 16 data (32%), negative impoliteness with 6 data (12%), and sarcasm with 4 data (8%). Additionally, the most dominant function of impoliteness that netizens used is affective impoliteness with 29 data (58%). It is followed coercive impoliteness with 11 data (22%), and entertaining impoliteness with 10 data (20%). These results indicate that impoliteness in social media does not only indicate rudeness but also as a way to attack someone. Specifically, this research shows that netizens use impoliteness in Instagram to express disagreement with Benny and Selena’s relationship.